ANALYSIS OF STUDENTS' MISCONCEPTIONS IN ANSWERING MULTIPLE CHOICE QUESTIONS ON MAGNETIC MATERIAL WITH THE HELP OF THE CERTAINTY OF RESPONSE INDEX METHOD - Fadilla Shafa Alyada Rahma; Nur Ngazizah; Titi Anjarini (Jurnal Cakrawala Pendas, 2025)
The continuity of the learning process in elementary schools cannot be separated from students' understanding of basic concepts, especially in Science. One of the important topics in science is magnetism. However, many students face difficulties in understanding this concept, which is often caused by misconceptions or misunderstandings related to magnetic phenomena. This study aims to analyze students' misconceptions in answering multiple choice questions on magnetic material with the help of the Certainty of Response Index (CRI) method as a measuring tool. This research approach is descriptive qualitative with the subject of 22 grade VI students from one of the private schools in Purwodadi District.  The results showed that 27% of students experienced misconceptions in magnetic material as a whole, with the highest misconceptions found in the indicator of determining materials that can be attracted by magnets at 55% and how to make magnets at 59%. In this study, the use of the CRI method can identify the level of understanding and misconceptions of students so that teachers can develop more effective strategies. The application of experiment-based learning and the use of interactive visual media can help reduce misconceptions and improve understanding of the concept of magnetism at the elementary school level.